Biomaterials constructed for MSC-derived extracellular vesicle loading and delivery—a promising method for tissue regeneration - Lu, Yu; Yang, Yu; Liu, Shiyu; Ge, Shaohua (Frontiers in Cell and Developmental Biology, 2022)
Mesenchymal stem cells (MSCs) become the preferred seed cells for tissue regeneration. Nevertheless, due to their immunogenicity and tumorigenicity, MSCs transplantation remains questionable. Extracellular vesicles (EVs) derived from MSC is becoming a promising substitute for MSCs. As a route of the MSC paracrine, EVs own nano-size and bilayer lipid-enclosed structure, which can guarantee the integrity of their cargoes, but EVs cannot obtain fully function in vivo because of the rapid biodegradation and clearance by phagocytosis. In order to improve the efficacy and targeting of EVs, methods have been proposed and put into practice, especially engineered vesicles and EVs controlled-release system. In particular, EVs can be cell or tissue targeting because they have cell-specific ligands on their surfaces, but the targeting ability may be eliminated by the biodegradation or phagocytic system during circulation. Novel application strategies have been proposed beyond direct injecting, EVs carriers such as biodegradable hydrogels and other loading systems have been applied in tissue regeneration, EVs engineering is also a brand-new method for higher efficacy. In this review, we distinctively summarize EVs engineering and loading system construction methods, emphasizing the targeting modification methods and controlled-release systems for EVs, which little literature reviews involved.